Design of Mirror Assembly for an Agile Reconfigurable Data Center Interconnect - Ghobadi, Manya; Mahajan, Ratul; Phanishayee, Amar; Blanche, Pierre-Alexandre; Rastegarfar, Houman; Glick, Madeleine; Kilper, Daniel (MSR Technical Report, 2016)
Free-space data center interconnects (wireless, optical) require a reflection mechanism to avoid obstacles/interference that can arise due concentrating signals in a plane consisting of source/destination nodes. A proper reflection mechanism above the communicating nodes enables a beam to depart the source, hit the reflector structure well above the source and destination, and head towards the desired destination by utilizing all three spatial dimensions. This technical report involves the design of a mirror assembly (i.e. reflector structure) for 3-D beam steering in data center networks that make use of the diffraction properties of Digital Micromirror Devices (DMDs).